Bone Densitometry Indices of Humerus Bone in Patients with Partial Rupture of the Supraspinatus Tendon - Strafun , S.S.; Bohdan , S.V.; Abbasov , S.M. (TERRA ORTHOPAEDICA, 2020)
Summary. Bone density is an important factor that affects the strength of the suture of the tendons of the rotator cuff. The higher the bone density is, the greater is the strength of fixation of the supraspinatus tendon to the bone, since the anchor is more securely fixed in the bone. Objective: to determine the bone mineral density of the proximal humeral epiphysis in patients with partial tear of the supraspinatus tendon. Materials and Methods. An X-ray examination of 48 shoulder joints (24 with partial tear of the supraspinatus tendon and 24 intact contralateral) was performed in 24 patients with partial tear of the supraspinatus tendon. On the electronic photographic prints of X-rays with the help of the specified software, 2 standard for all patients zones of determination of mineral density of bone tissue, both on the extremity with partial rupture of the supraspinatus tendon and on similar parts of the contralateral limb, were found. The bone mineral density (BMD) measurement zones were placed as follows: 1st zone - the greater tubercle of the humerus; 2nd zone - the middle of the humeral head. Each zone had a square shape and corresponded to 0.9±0.15 cm² of the area of the standard radiograph. Also, all patients underwent standard radiographic examination of the hip joints and lumbar spine. Conclusions: In zone 1 (the greater tubercle of the humerus), the bone mineral density of the limb with partial tear of the supraspinatus tendon reached 0.167±0.155 g/cm² and was slightly lower than that on the healthy limb 0.238±0.115 g/cm² (p<0.05). This indicates the effect of partial rupture of the supraspinatus tendon on the development of osteoporotic processes in the area of the greater tubercle of the humerus. In the 2nd zone (the middle of the humeral head), the average bone mineral density of the limb with partial rupture of the supraspinatus tendon reached 0.193±0.109 g/cm² and was also less than 0.245±0.159 g/cm² on the contralateral limb. In the 1st zone (the greater tubercle of the humerus), the dependence of changes in bone mineral density on the total changes in bone mineral density (r=0.62; p<0.01) was revealed. In zone 2 (r=0.14; p<0.01), bone mineral density was independent of overall changes in bone mineral density.